x < (y < z) = (x < y) < (x < z)
left distributive
x < (y > z) = (x < y) > (x < z)
left distributive
x < (y + z) = (x < y) + (x < z)
left distributive
x < (y & z) = (x < y) & (x < z)
left distributive
x < (y V z) = (x < y) V (x < z)
left distributive
(x < y) > z = (x > z) < (y > z)
right distributive
(x > y) > z = (x > z) > (y > z)
right distributive
(x + y) > z = (x > z) + (y > z)
right distributive
(x & y) > z = (x > z) & (y > z)
right distributive
(x V y) > z = (x > z) V (y > z)
right distributive
x & (y < z) = (x & y) < (x & z)
(x < y) & z = (x & z) < (y & z)
full distributive
x & (y > z) = (x & y) > (x & z)
(x > y) & z = (x & z) > (y & z)
full distributive
x & (y + z) = (x & y) + (x & z)
(x + y) & z = (x & z) + (y & z)
full distributive
x & (y & z) = (x & y) & (x & z)
(x & y) & z = (x & z) & (y & z)
full distributive
x & (y V z) = (x & y) V (x & z)
(x V y) & z = (x & z) V (y & z)
full distributive
x => (y & z) = (x => y) & (x => z)
left distributive
x => (y <=> z) = (x => y) <=> (x => z)
left distributive
x => (y => z) = (x => y) => (x => z)
left distributive
x => (y <= z) = (x => y) <= (x => z)
left distributive
x => (y V z) = (x => y) V (x => z)
left distributive
(x & y) <= z = (x <= z) & (y <= z)
right distributive
(x <=> y) <= z = (x <= z) <=> (y <= z)
right distributive
(x => y) <= z = (x <= z) => (y <= z)
right distributive
(x <= y) <= z = (x <= z) <= (y <= z)
right distributive
(x V y) <= z = (x <= z) V (y <= z)
right distributive
x V (y & z) = (x V y) & (x V z)
(x & y) V z = (x V z) & (y V z)
full distributive
x V (y <=> z) = (x V y) <=> (x V z)
(x <=> y) V z = (x V z) <=> (y V z)
full distributive
x V (y => z) = (x V y) => (x V z)
(x => y) V z = (x V z) => (y V z)
full distributive
x V (y <= z) = (x V y) <= (x V z)
(x <= y) V z = (x V z) <= (y V z)
full distributive
x V (y V z) = (x V y) V (x V z)
(x V y) V z = (x V z) V (y V z)
full distributive